Hydro-oceanographic condition (Tide, Sea Current, and Waves) of Nongsa Batam Sea - Sudra Irawan; Riza Fahmi; Muhammad Zainuddin Lubis; Satriya Bayu Aji; Arif Roziqin; Hanah Khoirunnisa (Journal of Applied Geospatial Information, 2018)
Tanjung Bemban is one of the seas found in the Nongsa sub-district, Batam city which is currently developed as a tourist attraction. This research aims to find out the hydro-oceanographic component, which consists of tide and the current and wave pattern in the sea of Tanjung Bemban Nongsa. To collect the data regarding tide, Tide Pole method, using measuring sign, is used, To collect data of sea current, Float Tracking (Lagrangian) method, by measuring distance and displacement of floating objects in the sea, is utilized, To collect the data of the wave, Wave Pole method, by measuring wave height, is employed. Based on the result of the research, it is clear that the tide of the sea is categorized as the semi diurnal, since there are two tides in one day with identical height, which occur sequentially and regularly. The highest flow reaches 260 cm and the lowest ebb 19 cm in the 4 days of observation, with 15 minutes interval. The measuring of ocean current is carried out for every 30-second intervals. Current velocity in Nongsa sea ranges from 0.02 m/s to 0.26 m/s. The current moves from east to southwest and west, even though some move northwest and north. Wave height is quite low, between 18 cm and 23 cm. Hydro-oceanographically, the Tanjung Bemban Nongsa area can be developed into a strategic tourism area